ANALISIS IMPLEMENTASI PEMASARAN PRODUK ASURANSI SYARIAH DALAM MENINGKATKAN PENJUALAN (KPM Prestasi Agency PT. Prudential Life Assurance Kota Medan) - Aisha Alvia; Fauzi Arif Lubis (Sekolah Tinggi Pariwisata Mataram, 2022)
Attracting the right customers and retaining them is very important for business success, therefore the need for a strategy in running a business, this strategy in order to achieve the company's predetermined business goals. In the marketing process is very necessary a strategy, strategy is a marketing process that is very important to run a business. Businesses must retain their clients, in order to remain profitable. The research on which this article is based investigates how marketing strategies carried out in the office (KPM) self-marketing achievements of PT agency. Prudential Life Assurance Medan. And whether the procedures used in this company are in accordance with islamic sharia principles. Qualitative research approach is used by researchers in carrying out this research, in this research researchers combine data by describing and describing a case in this prudential company. Marketing conducted by Prudential is how to market it directly to meet with clients and social media, services carried out in good ethics, polite and clear and open in conveying the products offered.